Hegel’s View on Fichte’s Aesthetical Conception (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: Hegel’s relation towards Fichte’s aesthetic conception can be clarified through three distinct perspectives. The first one examines the relation to the consequences of Kant’s aesthetic position, and it indirectly deals with Fichte’s role in these consequences to German idealism. The second one discusses Hegel’s critique of Fichte’s philosophy in general, from which it is possible to deduce his relationship towards the aesthetic phenomena in his philosophy. The third way examines the rare and sporadic topics in Hegel’s philosophical writings which directly reflect on Fichte’s aesthetic views. The author will try to combine all three of these perspectives and to provide a comprehensive insight into Hegel’s relation towards Fichte’s aesthetic position. Finally, it will be demonstrated that Fichte’s philosophy remains significant by the fact that it abolishes the dualism of Kant’s philosophy and provides the foundation for Hegel’s conception, in which the aesthetic field takes an important position.